Contemporary populist politics through the macroscopic lens of Randall Collins’s conflict theory - Schroeder, R (SAGE Publications, 2019)
This paper draws on Collins’s conflict theory to understand the contemporary surge of populism. It puts forward an account centred on citizenship rights and the state, and on ‘my nation first’ politics in four countries: the US, Sweden, India and China. Collins has identified a capitalist crisis, the dynamics of geopolitical legitimacy, and state-penetrating bureaucracy as three central processes in modern societies. Especially the last of these focuses attention on the conflict between cosmopolitan elites and ‘the people’, construed in exclusionary terms, which is on the rise in all of the four cases discussed here. The paper analyses the similarities and differences between them, and sketches the prospects for populist politics.